2014
DOI: 10.3390/s140813913
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter asburiae Strain L1: Complete Genome and Whole Genome Optical Mapping Analysis of a Quorum Sensing Bacterium

Abstract: Enterobacter asburiae L1 is a quorum sensing bacterium isolated from lettuce leaves. In this study, for the first time, the complete genome of E. asburiae L1 was sequenced using the single molecule real time sequencer (PacBio RSII) and the whole genome sequence was verified by using optical genome mapping (OpGen) technology. In our previous study, E. asburiae L1 has been reported to produce AHLs, suggesting the possibility of virulence factor regulation which is quorum sensing dependent. This evoked our intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…In previous work by Lau et al. (), the whole‐genome sequencing of E . asburiae strain L1 was performed using PacBio sequencing platform (Pacific Biosciences, Menlo Park, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work by Lau et al. (), the whole‐genome sequencing of E . asburiae strain L1 was performed using PacBio sequencing platform (Pacific Biosciences, Menlo Park, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel AHL‐producing Enterobacter asburiae strain L1 has been isolated from lettuce leaves and its genome was completely sequenced by PacBio sequencing platform. This isolate was found to secrete N ‐butanoyl homoserine lactone (C4‐HSL) and N –hexanoyl homoserine lactone (C6‐HSL) (Lau, Sulaiman, Chen, Yin, & Chan, ; Lau, Yin, & Chan, ). Previous studies have shown that E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in NGS instrumentation has enabled NGS to be performed using single molecules that generate long read lengths to yield complete genomes instead of draft genomes [19,20]. A complete genome will ease the downstream bioinformatics analysis for the accurate prediction of antimicrobial resistance genes, but, at present, the cost of obtaining a complete genome is still exorbitant [21][22][23].…”
mentioning
confidence: 99%
“…Colonies of strain RB-25 T were slightly raised with very pale white pigmentation on LB medium after 24 h of incubation. Gram staining of cells was performed using a Gram staining kit (Difco), and cell morphology was determined using a Hitachi TM3000 analytical tabletop microscope (Lau et al, 2014) in which the cells were observed to be Gram-stain-negative, motile and rodshaped (3-4Â7.5-9 µm) (Fig. S1, available in the online Supplementary Material).…”
mentioning
confidence: 99%